2012
DOI: 10.18624/e-tech.v0i0.208
|View full text |Cite
|
Sign up to set email alerts
|

Impacto financeiro das condenações post-mortem parciais e totais em uma empresa de abate de frango

Abstract: A carne de frango é um produto de origem animal de boa aceitação pelo consumidor, devido seu valor nutricional e seu preço acessível. Para que a indústria avícola aumente e melhore sua eficiência em produção dentro da filosofia de melhoria contínua, é preciso diminuir suas perdas durante a produção e o processamento. Grande parte destas perdas ocorre dentro do abatedouro, principalmente envolvendo as condenações parciais e totais das carcaças. As consequências diretas se expressam principalmente em perdas de q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Poor bleeding was also higher (p<0.01) in the winter (0.034) than in the summer (0.022), being characterized by red areas on the skin of the broiler carcass and resulting from failures in regulation of bleeding equipment or manual incision (Maschio & Raszl, 2012), compromising the microbiological and sensorial quality of the meat. Souza et al (2019) found 6.63% of condemnations for this cause, a value similar to that obtained for the winter, while Kanabata et al (2022) observed a 4.72% condemnation rate, similar to the value obtained for the summer.…”
Section: Condemnationmentioning
confidence: 99%
“…Poor bleeding was also higher (p<0.01) in the winter (0.034) than in the summer (0.022), being characterized by red areas on the skin of the broiler carcass and resulting from failures in regulation of bleeding equipment or manual incision (Maschio & Raszl, 2012), compromising the microbiological and sensorial quality of the meat. Souza et al (2019) found 6.63% of condemnations for this cause, a value similar to that obtained for the winter, while Kanabata et al (2022) observed a 4.72% condemnation rate, similar to the value obtained for the summer.…”
Section: Condemnationmentioning
confidence: 99%
“…Segundo Maschio;Raszl (2012), a perda econômica com as condenações totais e parciais dentro de um abatedouro avícola é de cerca de 1,7 milhões de reais ao ano.…”
Section: Introductionunclassified
“…A ocorrência de lesões que levam a condenação de carcaças é observada a todo momento por fiscais e agentes sanitários durante o abate, mas geram prejuízos para as empresas avícolas. A análise de fatores que influenciam as condenações de carcaças de frango auxilia a minimizar perdas e aperfeiçoar o processo de abate de frango, sendo possível ainda, uma visão mais crítica do processo industrial e da qualidade do frango vivo no campo (CANDIDO et al, 2021;MASCHIO, 2012).…”
Section: Introductionunclassified